ESSENTIALLY SMALL RIEMANN SUMS FUNGSI TERINTEGRAL HENSTOCK-DUNFORD PADA [a,b] - ., Solikhin; Sumanto, Y.D; Khabibah, Siti (MATEMATIKA, 2014)
In this paper we study Henstock-Dunford integral on [a,b]. We discuss some properties of the integrable. We shall define essentially small Riemann sums (ESRS)Â and show that it is necessary and sufficient condition for function to be Henstock-Dunford integral on [a,b].